Stadium city: an urban design plan for a transit-oriented development at the Truman Sports Complex - Ledgin, Alfred (Kansas State University, 2012)
The design of a transit-oriented development (TOD) is a major concern with regards to its functionality and prospects for success. The Truman Sports Complex in Kansas City, Missouri, home of two professional sports venues, has a unique location on a proposed transit corridor, the Rock Island. This corridor is planned to run between downtown Kansas City and suburban Lee's Summit. Therefore, the Truman Sports Complex site is a natural choice for a TOD. Building a TOD at the Truman Sports Complex will create a focal point on the Rock Island Corridor that connects Arrowhead and Kauffman Stadiums to downtown Kansas City and Lee's Summit via a regional transit system; bring together a diverse population through the creation of a walkable, mixed-use center located adjacent to the regionally known cultural institutions; and encourage new development around the junction of Interstates 70 and 435, a major transportation node in Kansas City, Missouri. This study, focusing on the design of such a project on this specific site, employs an extensive site analysis informing conceptual and specific planning ideas. It draws from a large body of literature and precedents, incorporating well established elements and principles into a new development that is both unprecedented in the Kansas City region and unique among TODs and sports-related districts. The main findings reveal the desirability of a strategy to develop on the existing parking surface of the Truman Sports Complex and reroute the Rock Island Corridor through the middle of the site so that it passes between the two stadiums. The final plan incorporates a mixed-use program, with retail, entertainment, offices, and apartments, into a variety of building types, including garden apartment buildings, low- to mid-rise mixed-use buildings, and high-rise towers, placed throughout the site in a compact, walkable grid pattern of streets. The significance of this project is that it can inform the Mid-America Regional Council, the Jackson County Sports Complex Authority, and other relevant stakeholders about the potential for developing on this site, and it demonstrates that a mixed-use, pedestrian-friendly, large-scale transit-oriented development with a wide variety of program is both viable and desirable at the Truman Sports Complex.
Keywords: Transit-oriented development; Urban design; Mixed-use; New urbanism; Transportation (0709); Urban Planning (0999)